ANALISIS KARAKTER IAN CURTIS DALAM FILM CONTROL KARYA ANTON CORBIJN - Nugraha, Purna Cipta (LANTERN (Journal on English Language, Culture and Literature), 2013)
Film Control talks about a band from England, Joy Division. It visualizes the band rise and process in musicality in the late 1970s. The film also puts the vocalist, Ian Curtis, as the main character. The purpose of this study is to analyze how the character, setting, and conflict build the visualization of Ian Curtis and how the internal and external conflicts affect the vocalist’s decision in the film Control directed by Anton Corbijn. Library research is conducted in this study, and the analysis employs an objective approach to discuss the intrinsic elements including character, setting, and conflict in the film. The study shows that Ian is depressed by many conflicts, some of which are the results of his own action. The position of Ian as the father and husband is not well fulfilled because of his duty in the band and this makes him feel guilty. His superego opposes his id when he has an affair with another woman as an escape from his burden. He keeps on questioning himself about what to do and what to decide. His epileptic condition is also a problem that makes his conflicts more complicated. As a result, Ian’s death instinct lead him to commit suicide and put an end to the unsolved problem.